PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Windy Yuvia; Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2023)
This study aims to obtain empirical evidence regarding the effect of return on equity, debt to asset ratio, total asset turnover, current ratio, net profit margin, and asset growth on firm value. The research data is sourced from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. The analytical method used is multiple regression analysis which is processed with the EViews 12 program. The results of this study indicate that return on equity has a positive and significant effect on firm value, debt to asset ratio has a positive and significant effect on firm value, total assets turnover is positive and not significant effect on firm value, current ratio has positive and significant effect on firm value, net profit margin has positive and significant effect on firm value, and asset growth has negative and significant effect on firm value.